Sistemas da internet e a proteção da privacidade do usuário: uma análise a partir dos termos de uso - Miranda, Yuri Paulino (2015)
The appearance and popularization of the internet has brought deep changes, bringing the possibility of great part of the social relations developing through data flows which travel within it. The collection and processing of this data is seen as essential for the technical and economical survival of the World Network. Many companies have today as main business, the use of this information which is collected from available applications on the internet that, not rarely, are offered for free to the public. The processing of this data, as done nowadays, reveals information which is contained in private scope, whereas the procedures involved, as well as the scale which is used, may defines a picture of surveillance, with social effects recognizably damaging. In this way, it is established a problem around the recognition of this data, the reason why the politics of site and application usages bring with them the authorization for collection and processing in an attempt to legitimize its use. Taking into consideration that the field of Information Science enables studies related to the utilization of informative technologies, its access and use, in this study we try to identify the current legal landscape related to the protection of intimacy and privacy, establishing the guidelines from there issued, from which a study of usage politics of some services are made, especially the one which mentions such protection. Some aspects related to difficulties to establish a concept of privacy are addressed, as well as the changes that their protection has known throughout time, notably in relation to technological innovations. From the analysis of the selected terms of use, we evaluated if the probability of the guidelines contained in them are compatible with the protection to privacy and if the consent manifested by its users is made with the view of information capable of providing, with the due clarity and precision, an understanding of the demonstration of will consequences. It is found however, that the terms used for the study serve much more to legitimize the indiscriminative use of collected data in the perspective of the appearance of new technologies and with that, new processing possibilities. Thereby, we suggest the adoption of a protection model which conjugates a certain degree of liberty to its user to control his own data, but from general guidelines established by the State, who should also be in charge of supervising its observance by the companies who are direct or indirectly responsible for the collection of data and processing of information.